Brief thief - Escoffier, Michaël, 1970- (Enchanted Lion Books, 2013)
"A lizard takes the liberty of using what seem to be some old underpants when he runs out of toilet paper. What he doesn't count on is that his own conscience and an outraged rabbit will be watching"--